2017
DOI: 10.1104/pp.16.01929
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-Acyl Carrier Protein Desaturase Mutations Uncover an Impact of Stearic Acid in Leaf and Nodule Structure

Abstract: Stearoyl-acyl carrier protein desaturase (SACPD-C) has been reported to control the accumulation of seed stearic acid; however, no study has previously reported its involvement in leaf stearic acid content and impact on leaf structure and morphology. A subset of an ethyl methanesulfonate mutagenized population of soybean () 'Forrest' was screened to identify mutants within the gene. Using a forward genetics approach, one nonsense and four missense mutants were identified to have high levels of seed, nodule, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…More deleterious alleles of SACPD‐C or additional variant genes influencing the accumulation of stearic acid may elevate stearic acid to the desired levels, with or without the high oleic acid trait. Recent research has demonstrated large effects on nodule development when seed stearic acid levels are altered, so achieving the threshold in soybeans without ultimately sacrificing yield may be problematic (Gillman et al, ; Lakhssassi et al, ). The two major quantitative trait loci besides the null allele of SACPD‐C contributing to greater than 20% stearic acid levels from soybean breeding line A6 have not yet been evaluated in a high oleic acid background (Heim & Gillman, ).…”
Section: Discussionmentioning
confidence: 99%
“…More deleterious alleles of SACPD‐C or additional variant genes influencing the accumulation of stearic acid may elevate stearic acid to the desired levels, with or without the high oleic acid trait. Recent research has demonstrated large effects on nodule development when seed stearic acid levels are altered, so achieving the threshold in soybeans without ultimately sacrificing yield may be problematic (Gillman et al, ; Lakhssassi et al, ). The two major quantitative trait loci besides the null allele of SACPD‐C contributing to greater than 20% stearic acid levels from soybean breeding line A6 have not yet been evaluated in a high oleic acid background (Heim & Gillman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, neofunctionalized SACPD gene copies in oleaster are likely also responsible for the differences in oleic-and linoleic-acid contents of olive and sesame (19,30). Recently, it was observed that mutations in the soybean SACPD-C gene promote higher accumulation of leaf stearic-acid content, as well as changes in leaf structure and morphology (31). Therefore, SACPD1 and 2, which are highly expressed in leaves, might be related with leaf morphology as well as oleicacid accumulation in fruit with overexpressed levels of SACPD7 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the development of soybean high‐density markers from large sequencing data sets provides a powerful tool for whole‐genome prediction and selection applications (Patil et al ., ). In SCN resistance, remarkable progress has been made since the cloning of the resistance genes that reside in the two major loci, rhg1 and Rhg4 (Cook et al ., ; Lakhssassi et al ., 2017a; Liu et al ., , 2017) . However, the mechanism of SCN broad‐based resistance and the interaction of these two loci in soybean accessions are still unclear and warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%